2019
DOI: 10.1097/paf.0000000000000439
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Craniometric Sexual Dimorphism Using Multidetector Computed Tomographic Imaging in a Sample of Egyptian Population

Abstract: Sex determination is an initial and essential component of any medicolegal investigations. However, sometimes only cranial remains are available. The objective of this study was to determine sex using 12 craniofacial measurements in multidetector computed tomographic images of 150 Egyptian subjects (80 men and 70 women), with age ranging from 18 to 60 years. The results revealed a significant increase in the mean of all craniofacial measurements in men in comparison with women (P < 0.05). Bizygomatic breadt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 18 publications
4
11
0
Order By: Relevance
“…The observed parameters of the orbital height and width had a tendency to be higher on the right side, leading to the higher values of the left orbital index (right: 88.2 ± 6.7, left: 90.5 ± 6.3; p = 0.019, t-test). This is in accordance with the earlier findings and widely accepted theory that the scull and the face right/left asymmetry with higher values of the right orbital measures are the consequence of the brain asymmetry and the dominance of the left hemisphere [24,25].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The observed parameters of the orbital height and width had a tendency to be higher on the right side, leading to the higher values of the left orbital index (right: 88.2 ± 6.7, left: 90.5 ± 6.3; p = 0.019, t-test). This is in accordance with the earlier findings and widely accepted theory that the scull and the face right/left asymmetry with higher values of the right orbital measures are the consequence of the brain asymmetry and the dominance of the left hemisphere [24,25].…”
Section: Discussionsupporting
confidence: 93%
“…Thus, it is possible to speculate that the lack of sexual dimorphism in Roma population influenced our results. The results of our study confirmed the earlier findings in variation of orbital dimensions between the left and right side [18,24]. The observed parameters of the orbital height and width had a tendency to be higher on the right side, leading to the higher values of the left orbital index (right: 88.2 ± 6.7, left: 90.5 ± 6.3; p = 0.019, t-test).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Literature Literature Literature Orbit Volume (cm 3 ) 24.3 [43] � 25.6 [62] � 26.8 [63] 25-28.9 [13,[45][46][47] 27.7 [64] 33.2 [65] 26.8 [49] 27.8 [66] 29.6 [50] 29.2 [64] 23.2 [51] 26.5 [49] 25.6 [66] 25.9 [64] Orbit width 39.7 [67] � 39.8 [52] -41.3 [53] 41.7 [64] 35 [68] 39.8 [54] 41 [69] 42.5 [64] 44.2 [55] 33.6 [68] 36.9 [54] 39 [69] 41 [64] 42.1 [54] Orbit height 2 (Inf-SupM) 33.4 [52] 34.1 [64] 36.2 [67] � 36.6 [45] 32.4 [10] 33.6 [64] 35.9 [56] 36.6 [68] 39 [69] 31.8 [10] 34.1 [64] 35.4 [56] 35.7 [68] 37 [69] Orbit lenght medial 41.3 [61] � [64] 43 [57] 46.9…”
Section: All Groups Male Femalementioning
confidence: 99%
“…These accuracies are in agreement with previous research conducted on geographically narrower assemblages, adopting population‐specific equations. For example, the combination of multiple cranial measurements reached an accuracy of 77%–80% in South Africans (Franklin et al, 2005), 80% in Egyptians (Adel et al, 2019), 82% in Brazilians (Matamala et al, 2009), 84% in Japanese (İşcan et al, 1995), 85.5%–85.7% in Indians (Ramamoorthy et al, 2016; Saini et al, 2011), 86% in South African Whites (Steyn & İşcan, 1998), 87% in Turks (Ekizoglu et al, 2016), 88.2% in Greeks (Kranioti et al, 2008), 90% in Tunisians (Zaafrane et al, 2018), and 90.6% in Thais (Mahakkanukrauh et al, 2015). Regarding postcranial data, humeral measurements showed accuracies up to 86.8% in Chinese, 92.4% in Japanese, and 97.1% in Thai groups (İşcan et al, 1998), as well as 96% in South African Whites and 95% in South African Blacks (Steyn & İşcan, 1999) and 92.9% in Greeks (Kranioti & Michalodimitrakis, 2009).…”
Section: Discussionmentioning
confidence: 99%